Regulatory T cell CD4 ‏&CD25‏ expression and chemokine C-X-C ligand 13 level before and after corticosteroid therapy in pediatric ITP patients - Heba A. Ahmed; Eman Mohamed Fahmy; Eman M. Nagiub Abdelsalam (Elsevier, 2019)
Childhood Idiopathic thrombocytopenic purpura (ITP) is one of the most commons autoimmune bleeding disorders characterized by isolated, immune-mediated low platelet count, the T-follicular helper (Tfh) cells are a subset of effector CD4 (+) T cells, that plays a pivotal role in maintaining self-tolerance, deregulation of Tfh activities has a key role in immune process taking place in ITP in which the production of platelet autoantibodies might be caused by cytokine network dysregulation. The objective of our study was to analyze the relationship of Tfh cells CD4&CD25 and C-X-C ligand 13 (CXCL13) expressions before and after steroid thereby in pediatric ITP. Material and method: the study included 45 pediatric patients with acute ITP and 20 healthy controls; we used flowcytometry to assess percentages of CD4‏ and CD25‏ cells as markers of regulatory T cells, also, the serum level of interleukin- CXCL13 was measured by ELISA at diagnosis and after 4 weeks receiving corticosteroid. Results: the expression of CD4‏ & CD25‏ ‏ markers were significantly reduced in ITP cases, who also showed an elevated CXCL13 level in comparison to controls, however, the level of CXCL13 declined after treatment, the CXCL13 optimum cut off point for predicting ITP response to therapy was determined to be 90 pg/ml with AUC 0.976, Sensitivity 88.89% and Specificity 100% P-value < 0.00. Conclusion: Serum CXCL-13 levels could be used as a significant predictor of response to therapy in ITP patients, CD4&‏CD25 expression has a role in the pathogenesis of childhood acute ITP principally linked to the level of platelet count drop. Keywords: Immune thrombocytopenia (ITP), Flowcytometry, T follicular helper cells, CXCL-13 chemokine, Pediatric, Autoimmune disease